PREVALENCE OF CONGENITAL HEART DISEASE IN RURAL COMMUNITIES OF PAKISTAN - Rizvi, Syed Faiz-ul- Hassan; Mustafa, Ghulam; Kundi, Asadullaha; Khan, Mushtaq Ahmed (Journal of Ayub Medical College Abbottabad, 2015)
Background: Prevalence of Congenital Heart Disease (CHD) is well established in most of the developed countries, where childbirth is obligatory in hospitals and allied facilities. In rural Pakistan the situation is reverse, where most of deliveries take place in homes by traditional birth attendants’ therefore true prevalence of CHD in our population is unknown. In rural Pakistan almost 80% children are born at home hence the figures are unknown. This study was designed, to determine the prevalence of congenital heart disease in rural Pakistan. Methods: During a cross-sectional survey of rural population belonging to major ethnic groups living in three provinces of Pakistan to determine the prevalence of rheumatic heart disease (RHD), CHD rates were calculated as a sub study. Nine thousand four hundred and seventy-six (9476) subjects of all ages were screened using cluster sampling technique. Socio-demographic variables were recorded. Auscultation and short physical examination performed for initial screening and final diagnosis was confirmed on M-mode/2D/Doppler. Results: Thirty two patients had RHD, 25 Patients identified with CHD and another 7 patients had mixed CHD & RHD. Overall prevalence for CHD was 3.4/1000. The commonest lesion was Atrial Septal Defect (ASD) 40%, Ventricular Septal Defect (VSD) 35%, Aortic Stenosis (AS) 10%, Atrio Ventricular Septal Defect (AVSD) 5%. Conclusion: This is the first study to report CHD prevalence from multiethnic representative sample from rural communities of Pakistan. Apparently CHD rate seems less compared with facility based data because records of still stillbirths are not available and autopsies are not performed as routine. Very high infant mortality from rural areas of Pakistan also favours high prevalence for CHD; however these figures represent an overall picture of CHD in a community where medical facilities are lacking. Keywords: congenital heart disease, Prevalence, Rural communities